Types of traumatic dental injuries to the primary dentition and the surface against which they occurred - CASTILLO SÁNCHEZ,Linda Patricia (2019)
ABSTRACT Objectives The aims of this retrospective study were to investigate the types of traumatic dental injury recorded in an oral health service within a ten-year period and to report the type of surface against which the traumatic dental injury occurred. Methods Dental records from children assisted in the Dental Trauma Clinic at the Rio de Janeiro State University’s School of Dentistry, between 2006 and 2016, were analyzed. Only those records who had registered some type of trauma in the primary anterior teeth (incisors and canines) and aged 0-96 months at the time of trauma were considered eligible for the study. Results Four hundred and eighty-three dental records were included, totalizing 786 traumatized teeth. The average age when traumatic dental injury occurred was 37.25 months (±18.62). Enamel fractures (32.8%) and intrusive luxations (45.6%) were the most prevalent types of trauma. The majority of traumas occurred against ceramic surfaces (34%). The greatest number of teeth with lateral luxation were the ones that hit against a ceramic surface (p=0.014; U Mann-Whitney test). According to this study, the most prevalent type of trauma in the dental tissue and pulp was enamel fracture and in the periodontal tissue was intrusive luxation. The majority of traumas occurred due to falls, at home and against ceramic surfaces. Conclusion The results showed that a high frequency of the lateral luxation was associated to a traumatic impact against ceramic surfaces.